Research handbook on law and religion - Ahdar, Rex J. (Edward Elgar Publishing, 2018)
Offering an interdisciplinary, international and philosophical perspective, this comprehensive Research Handbook explores both perennial and recent legal issues that concern the modern state and its interaction with religious communities and individuals. Providing in-depth, original analysis the book includes studies of a wide array of nation states, such as India and Turkey, which each have their own complex issues centred on law, religion and the interactions between the two. Longstanding issues of religious liberty are explored such as the right of conscientious objection, religious confession privilege and the wearing of religious apparel. The contested meanings of the secular state and religious neutrality are revisited from different perspectives and the reality of the international human rights protections for religious freedom are analysed. Timely and astute, this discerning Research Handbook will be a valuable resource for both academics and researchers interested in the many topics surrounding law and religion. Lawyers and practitioners will also appreciate the clarity with which the rights of religious liberty, and the challenges in making these compatible with state law, are presented.